An investigation of the generalisability of buoyancy from academics to athletics - Calhoun, J. V.; Kipling Webster, E.; Garn, A. C. (International Journal of Sport and Exercise Psychology, 2019)
Buoyancy, the ability of an individual to handle everyday setbacks, has been applied successfully to academics. The purposes of this study were to determine if buoyancy can be successfully applied to the domain of sports (i.e. athletic buoyancy), to examine the relationship between academic and athletic buoyancy, and to determine the efficacy of five sport-oriented predictors (5Cs), confidence, coordination, commitment, composure, and control, on both athletic and academic buoyancy. Collegiate sport club athletes (N = 285) completed a one-time survey assessing their athletic buoyancy, academic buoyancy, and each of the sport-oriented 5Cs. Results supported a two-factor buoyancy model, with a moderate correlation (r = .61) between the two latent factors. Multiple linear regressions revealed that the 5Cs model accounted for 26% of the variance in athletic buoyancy, and 15% of the variance in academic buoyancy. Sport composure was the only significant predictor of athletic buoyancy, while sport confidence and sport composure were both significant predictors of academic buoyancy. Sport composure positively predicted both academic and athletic buoyancy, though the magnitude varied by domain. These results indicate a multidimensional buoyancy structure and generalisability across academic and athletic domains, with potential implications for athletic performance and training, adaptability, and well-being in sport.